2020
DOI: 10.1016/j.ptsp.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomised observational study of individualised variations in the start position of the closed-kinetic chain upper extremity stability test

Abstract: To assess the reliability, precision and differences between scores produced using the standard 36" start position and 3 modified start positions of the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), towards normalization to the individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Recently authors have suggested that placement of the hands in the starting position should correspond to the anthropometric characteristics of the participant. 20,28 The participant was asked to move as quickly as possible alternating their reach to each piece of tape. A warmup trial was done to familiarize each participant before the three trials of the test.…”
Section: Malementioning
confidence: 99%
See 4 more Smart Citations
“…Recently authors have suggested that placement of the hands in the starting position should correspond to the anthropometric characteristics of the participant. 20,28 The participant was asked to move as quickly as possible alternating their reach to each piece of tape. A warmup trial was done to familiarize each participant before the three trials of the test.…”
Section: Malementioning
confidence: 99%
“…10 The majority of these studies have examined test-retest reliability and three of these studies investigated and reported the average number of touches, normalized score, and power score. 20,22,28 A Comparison of Resting Scapular Posture and the Davies Closed Kinetic Chain Upper Extremity Stability Test Use of the power score and normalized score requires further investigation. Goldbeck and Davies 12 first described the power score using 68% of the participant's weight in kilograms based on Dempster's work.…”
Section: Investigated Four Different Positions (At Restmentioning
confidence: 99%
See 3 more Smart Citations